Communication Strategy of Social Assistance Officers With Assisted Residents at Bina Laras Harapan Sentosa 2 Social Institution - Chandra Puspa Pamungkas; Lany Widyastuti (Jurnal Indonesia Sosial Teknologi, 2024)
This research was motivated by the large number of inmates at the Bina Laras Harapan Sentosa 2 Social Home, the majority of whom came from the streets. With the different educational backgrounds of the accompanying officers, the process of extracting data and information from the inmates is a challenge in itself. What is the communication strategy used by social assistants in the assessment process with inmates? If the communication strategy is carried out correctly, the process of extracting information from the inmates will run according to expectations and make the service and rehabilitation process run according to the SOP. The theory used in this research uses Communication Accommodation Theory and Social Learning Theory. This is based on the observation that officers and inmates appear to imitate each other's behavior and the behavior adopted is based on the environment and the behavior of other people around them. This study used qualitative research methods. This research concludes that the communication strategy carried out by the assistants was successful in accordance with expectations. This can be seen from the data and information obtained which is adequate and the assisted residents can receive services and rehabilitation according to the criteria, and quite a lot have been successfully reunified with their families.